Transient landscapes: insights on a changing planet - Wohl, Ellen E., author; University Press of Colorado, publisher (Colorado State University. Libraries, 2015)
Landscape-the unique combination of landforms, plants, animals, and weather that compose any natural place-is inherently transient. Each essay in Transient landscapes, Wohl introduces this idea of an ever-shifting, ever-transitioning global landscape, revealing how to see the ubiquity of landscape transience, both that which results through the earth's natural environmental and climatological process and which comes from human intervention.--Provided by publisher.
Keywords: Geodynamics; Landscape changes; Environmental geomorphology